Innovative School Leadership Aspects (Journal of Legal Studies, 2023)
This study examines the managerial role of five school principals in Tbilisi in sustaining success and innovation. It describes the management and leadership practices of five school principals, who are considered to be innovative, well-managed, with excellent academic results, and highlights the principals' own contributions for school innovation and success. The study used the case study method based on the qualitative research method. At each school, opinions on school governance were gathered through individual interviews with the school principal, representatives of local resource centers, and other members of the school board. students and members of the school community. This study provides insight into organizational culture and school changes, as well as the principal role of principals in creating and managing a successful and innovative school. The study uses stakeholder perspectives on school leadership and school performance to provide us with insight into school management in each case, as well as draw attention to differences and similarities between different cases. The research findings highlight the importance of principals' life experiences in determining their management style and values. Innovative principals identify five common aspects of leadership and related behaviors that characterize their leadership style and underpin the success of their schools. Furthermore, innovation schools have common characteristics. A map of how the principal's management style and school innovation and success, life experience, five managerial aspects and corresponding behaviors, and other elements of school success are related to innovative aspects of management and leadership has been developed. Realizing what works in successful and innovative schools is the preliminary step in determining how to direct the practice of such schools to those parts of the school that require this experience. The current study demonstrates an innovative management style, demonstrating that some principals are very successful in creating an innovative culture, including behavioral patterns that can be learned and used by people aspiring to innovative and successful school management.